The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1016/0014-5793(92)81343-k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small Na+/H+ exchanger‐like message in the rabbit myocardium

Abstract: We examined 1he Na*/H+ exchanger message in isolated perfused rabbi1 hear15 using Northern blot analysis with cDNA encoding for the rabbit cardiac Na*/H* exchanger. A cDNA probe from the coding region of the rabbit myocardial Na'Al' exchanger hybridized to mRNA of 5 kb under high stringency, and to a second 3.8 kb mRNA species under low stringency. When Northern blots were re-probed with a section of the 3'-untransla1ed region of the cDNA, the 5 kb message w3s apparent while 1hc smaller 3.8 kb message was nol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…In addition to these in silico analyses, support for alternate splicing can be found in previous work. First, early after the cloning of NHE1, short-length transcripts have been described in rabbit myocardium (Dyck et al 1992). Second, amongst two alternate transcripts detected in brain and lung from engineered Slc9A1 knockout mice, one was shown to have an in-phase downstream sequence that can produce an intact C-terminus peptide (Bell et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these in silico analyses, support for alternate splicing can be found in previous work. First, early after the cloning of NHE1, short-length transcripts have been described in rabbit myocardium (Dyck et al 1992). Second, amongst two alternate transcripts detected in brain and lung from engineered Slc9A1 knockout mice, one was shown to have an in-phase downstream sequence that can produce an intact C-terminus peptide (Bell et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Northern analysis revealed a message in testis which is smaller than the NHE-1 message in other tissues [26]. Dyck et al [45] recently reported a smaller (3.8 kb) message in ischaemic hearts. This message hybridized with different NHE-l cDNA probes derived from the open reading frame but not from the untranslated regions.…”
Section: The Na+/h+ Exchanger and Its Isoformsmentioning
confidence: 99%
“…When rat hearts are subjected to relatively short periods of ischaemia, intracellular acidosis occurs. This results in a small increase in NHE-I mRNA levels and a larger increase in a related isoform (3.8 kb) of the message [45]. Primary cultures of isolated myocytes also increase Na+/H+ exchanger activity in response to exposure to external media of low pH (L. Fliegel, unpublished work).…”
Section: Regulation Of the Na+/h+ Exchangermentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac cells do not possess NHE2–5 [ 46 , 47 , 48 , 49 ] and NHE6–9 are localized to intracellular organelle membranes such as mitochondria, endosomes and the Golgi network so they do not directly contribute to proton extrusion from cardiomyocytes [ 50 , 51 ]. cDNA for NHE1 codes for the identical NHE1 message as in other tissues [ 29 ] and though a different size mRNA for NHE1 has been shown to occur in ischemic conditions [ 52 ], this does not code for a functional protein. exchange has been clearly demonstrated in cardiac sarcolemma vesicles where it was inhibited by amiloride [ 28 , 53 ].…”
Section: Expression and Localization Of Myocardial Nhe1mentioning
confidence: 99%